Archiwum i „papiery” Erny Rosenstein — „próba porządkowania doświadczeń” - Juchniewicz, Andrzej (Zagadnienia Rodzajów Literackich, 2025)
The article’s author analyzes the contents of Erna Rosenstein’s private archive, deposited in the Manuscript Warehouse at the National Library in Warsaw. Its contents consist of five notebooks, one notebook decorated by the artist, two binders with poems, postcards and letters addressed to Józef Baran and one photo of Rosenstein. The contents of the rough drafts have never been published, but in 2002, Zbigniew Taranienko printed several poems from the archive in the publication “Things, Traces, and Papers from the Cabinet”. The author of the essay, analyzing Rosenstein’s private notes, proposed a narrative “from the inside of the archive” (Lucyna Marzec’s term). Individual notes made it possible to reconstruct the rhythm of the artist’s life in the 1990s and establish a list of people with whom she kept in touch. In addition, the notebooks from the archive provide an insight into the artist’s creative process, who would have prioritized notes and drawings. On individual pages, you can find lists (names, numbers, products), instructions and drawings prepared by the artist. Rosenstein’s way of keeping rough drafts indicates the artist’s reluctance to separate the two activities and to separate what is written and drawn. The artist’s archive allows her to tell stories about her private life and artistic activity and trace how the notes were organized, which took the form of Silva. Rosenstein’s rough drafts store poetic texts and sketches transferred to canvas and are also an enclave of freedom and manual activities, including copying, pasting, and cutting. The book she created, containing poems from the 1990s, can be considered a summa of reflections on art and literary activities.